Suicide rate following attendance at an accident and emergency department with deliberate self harm. Issue 2 (March 1996) - Ryan, J; Rushdy, A; Perez-Avila, C A; Allison, R
Abstract : OBJECTIVE--To determine the risk of suicide in patients attending an accident and emergency (A&E) department with deliberate self harm. METHODS--Information was obtained on suicides and open verdicts from the coroner's office and cross checked with computerised records in the A&E department. RESULTS--There was a trend to suicide among younger socially isolated males and older females. CONCLUSIONS--There is a significant association between suicide and a previous attendance at A&E with deliberate self harm. Appropriate assessment of these patients is an efficient way of managing self harm.